The concept of sport sampling versus sport specialization: Preventing youth athlete injury: A systematic review and meta-analysis - Carder, S. L.; Giusti, N. E.; Vopat, L. M.; Tarakemeh, A.; Baker, J.; Vopat, B. G.; Mulcahey, M. K. (The American Journal of Sports Medicine, 2020)
Background: The prevalence of youth athletes specializing in 1 sport has been increasing over the past decade. Subsequently, the rate of youth athlete injury has also been increasing. It is possible that an association exists between youth specialization and sports injury rate. Purpose: To determine if sport sampling is associated with a lower sports injury rate in youths compared with youths who specialize in 1 sport. Study Design: Systematic review and meta-analysis. Methods: A systematic review was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines using PubMed, Embase, and the Cochrane library. Inclusion criteria included studies written in the English language, studies with athletes between 7 and 18 years of age, studies that report injury rates, and studies that specify if athletes were sport samplers or specialized in a sport. Data relevant to this study, including injuries and patient characteristics, were extracted and statistically analyzed. Results: The initial search identified 324 studies, 6 of which met inclusion criteria. From these 6 studies, the total participant number was 5736. Of those, 2451 (42.7%) were "sport samplers," 1628 (28.4%) were "sport specializers," and 1657 (28.9%) were considered "others" (ie, could not be classified as true samplers or true specializers). The average age of all the athletes was 14.6 years (range, 7-18 years). Sport specializers had a significantly higher injury risk than the sport samplers (RR, 1.37; 95% CI, 1.19-1.57; P < .0001). There was a higher risk of injury in the "others" group when compared with the "sport sampler" group (RR, 1.21; 95% CI, 1.14-1.29; P < .0001). There was a higher risk of injury in the "sport specializer" group over the "others" group (RR, 1.09; 95% CI, 1.04-1.14; P < .005). Conclusion: Sport sampling is associated with a decreased risk of sports injury in youth athletes when compared with those who specialize in 1 sport. Injury rates increase as a youth athlete becomes increasingly specialized. Youth athletes would benefit substantially from participating in sport sampling.